2019
DOI: 10.1021/acs.est.8b05592
|View full text |Cite
|
Sign up to set email alerts
|

Hormones and Pharmaceuticals in Groundwater Used As a Source of Drinking Water Across the United States

Abstract: This is the first large-scale, systematic assessment of hormone and pharmaceutical occurrence in groundwater used for drinking across the United States. Samples from 1091 sites in Principal Aquifers representing 60% of the volume pumped for drinking-water supply had final data for 21 hormones and 103 pharmaceuticals. At least one compound was detected at 5.9% of 844 sites representing the resource used for public supply across the entirety of 15 Principal Aquifers, and at 11.3% of 247 sites representing the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(77 citation statements)
references
References 52 publications
1
72
0
Order By: Relevance
“…Literature information from other studies shows that BPA and DEET were identified as the most commonly detected ECs in groundwater [32][33][34][35][36] with BPH being previously identified as one of the most widespread ECs in groundwater located under MSW landfills [31,[37][38][39]. Table 5.…”
Section: Groundwater Analysismentioning
confidence: 99%
“…Literature information from other studies shows that BPA and DEET were identified as the most commonly detected ECs in groundwater [32][33][34][35][36] with BPH being previously identified as one of the most widespread ECs in groundwater located under MSW landfills [31,[37][38][39]. Table 5.…”
Section: Groundwater Analysismentioning
confidence: 99%
“…Bexfield et al. ( 2019 ) also reported that compounds with high or low values tended to be present in groundwater.…”
Section: Discussionmentioning
confidence: 97%
“…Well depth is an important factor influencing the concentrations of pharmaceuticals in groundwater. Studies have reported higher concentrations and frequencies of detection in shallow wells with depths typically <23 m in comparison with deeper wells (Verstraeten et al, 2005; Barnes et al, 2008; Bexfield et al, 2019). However, in the present study, no correlation was observed between well depth and concentrations of pharmaceuticals.…”
Section: Discussionmentioning
confidence: 99%